Factors Affecting Development of Peroxisomes and Glycolate Metabolism among Algae of Different Evolutionary Lines of the Prasinophyceae. - Kehlenbeck, P. (1995)
Leaf-type peroxisomes are not present in the primitive unicellular Prasinophycean line of algae but are present in the multicellular algae Mougeotia, Chara, and Nitella, which are in the one evolutionary line, Charophyceae, that led to higher plants. Processes related to glycolate metabolism that may have been modified or induced with the appearance of peroxisomes have been examined. The algal dissolved inorganic carbon-concentrating mechanism and alkalization of the medium during photosynthesis were not lost when peroxisomes appeared in the members of the Charophycean line of algae. Therefore, it is unlikely that lowering of the CO2 concentration in the environment was a major factor in the evolutionary appearance of peroxisomes. Multicellular Mougeotia, early members of the Charophycean line of algae, have peroxisomes, but they excrete excess glycolate into the medium. The cytosolic pyruvate reductase for D-lactate synthesis and the glycolate dehydrogenase activity almost disappeared when peroxisomal glycolate oxidase, which also oxidizes L-lactate, appeared. These biochemical changes do not indicate what caused the induction of leaf-type peroxisomes in this evolutionary line of algae. The oxygenase activity of ribulose-1,5-bisphosphate carboxylase/oxygenase and glycolate oxidase require about 200 to 400 [mu]M O2 for 0.5 Vmax. These high-O2-requiring steps in glycolate metabolism would have functioned faster with increasing atmospheric O2, which might have been the causative factor in the induction of peroxisomes.